Operational Excellence by Implementation of 5S Concepts and Lean Management Practices in Vivarium (Journal of Laboratory Animal Science, 2024)
Modern vivarium operation requires collective efforts by cross-functional teams especially within the  collaborative research organizations for the successful outcomes of comprehensive laboratory animal care  program. The drug discovery with rapid screening turnovers and innovative approaches demands infrastructure expansion by increasing several other capabilities in vivarium. The strategic portfolio changes  and therapeutic areas closure retained several high-end equipment’s left unused that eventually occupied  space in the barrier system which intricate daily operations and space management became challenging  over the period. The vivarium facility was under continuous improvement by the quality assurance program  based on monthly independent audit reports and compiled the compliance including animal welfare  standards of at least 5 years period. Corporate initiatives such as Kaizen events, 5S concepts, Gemba walk  and green labs certifications were implemented systematically at various phases across the organization  including vivarium. The leadership team was a driving force behind the lean management practices and its  implementation. The quality assurance program was able to bring out several improved operational  processes notably by creating an additional quarantine space; repurposing high-end equipment for other  investigators to support their ongoing programs; effective space utilization by creating in-house diagnostic  laboratory; donating low-density animal racks for academic institutions as part of educational outreach  efforts; containment of solid radioactive waste disposal by compaction process for longer half-life  radioisotopes. In conclusion, lean management practices collectively demonstrated a measurable  outcome in terms of continuous process improvement, effective vivarium management by ensuring  compliance based on periodical observations without compromising animal welfare, conservation of  energy and resources, effective space utilization and systematic implementation of 5S concepts by  repurposing of equipment to other laboratories. Overall, the system-driven process has improved the  standards with better performance that eventually enhanced the quality and productivity at the laboratory  animal facility
Keywords: Lean Management; Quality Assurance; Kaizen Events; Gemba Walk; 5S Concepts; Process Improvements